A PROBLEM ANALYSIS AND TEACHERS STRATEGIES TO IMPROVE WRITING (GREETINGS CARD) SKILLS FOR JUNIOR HIGH SCHOOL IN SMP NEGERI 9 PEMATANGSIANTAR - MONIKA F. K. PURBA; ESTER TRESIA SIANTURI; DANIEL R. SIAHAAN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
This research started from the problem of the less skills of students in writing, especially in the use of grammar in students of SMP N 9 Pematangsiantar. The purpose of this research is to see the progress in student abilities in writing skill through Greetings card, as well as to find the difficulties faced by students. This research is quantitative research. The population in this study were students of class VIII SMP N 9 Pematangsiantar. The instrument used is a writing test. Data from students' writing tests were analyzed based on indicators and then interpreted and became research findings. From the results of this study, it was found that students had weak abilities in writing Greetings card. Based on the tests that have been given, it was also found difficulties faced by students when writing greetings card, namely in the use of language. This difficulty relates to the use of the tenses, action verbs, linking verbs, and pronouns. The causes of this difficulty are interlingual transfer, intralingual transfer, and the lack of vocabulary possessed by students. So it can be concluded that students still have many difficulties in writing a good and correct sentence in Greetings card according to the applicable rules. Furthermore, based on the results of this study, it is expected that teachers can provide better teaching techniques and students can do more exercises to improve students' writing skills.